2015
DOI: 10.1016/j.ajo.2014.11.028
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Dry Eye Disease and Depression and Anxiety in a Large Population-Based Study

Abstract: Purpose To investigate the association between dry eye disease and each of depression and anxiety. Design Retrospective, case-control study Methods Setting University of North Carolina outpatient clinics Study Population All patients over the age of 18 years old seen between July of 2008 and June of 2013 were included in the analysis. Observation Procedure Cases were defined according to ICD-9 diagnosis codes for dry eye disease, anxiety, and depression. Outcome Measure Separate odds ratios were cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
68
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(80 citation statements)
references
References 30 publications
0
68
0
2
Order By: Relevance
“…Recently, DES has been linked to psychological distress in a large population-based retrospective study. 27 However, it is not clear from previous studies, which symptoms and signs of dry eye are associated with signs of psychological distress. These associations, if known, may have implications in the management of psychological distress among dry eye patients and provide insight into the relationship between dry eye and psychological syndromes.…”
Section: Introductionmentioning
confidence: 95%
“…Recently, DES has been linked to psychological distress in a large population-based retrospective study. 27 However, it is not clear from previous studies, which symptoms and signs of dry eye are associated with signs of psychological distress. These associations, if known, may have implications in the management of psychological distress among dry eye patients and provide insight into the relationship between dry eye and psychological syndromes.…”
Section: Introductionmentioning
confidence: 95%
“…Very recently, one large population-based study of all age groups also identified a statistically significant association between DED and each of depression and anxiety. 18 The purpose of this study was to determine the prevalence of depression in patients with DED and the nature of the relationship between depression and DED in Korean women. The Korea National Health and Nutrition Examination Survey (KNHANES) enables the examination of extensive data on health and socioeconomic status using a large population in Korea.…”
mentioning
confidence: 99%
“…However, if this was the case, then eye care practitioners would never be able to explain the cause of these symptoms by simply using standard ophthalmic examinations. In fact, some investigators have reported finding a significant relationship between a patient's symptoms and their psychogenic status, such as depression, anxiety, or a subjective happiness feeling [511, 18], which suggests these relationships may need to be taken into consideration. In addition, sensitivity to pain has been reported to play a significant role in the severity of the DED complaints [12, 13], which also suggests importance of the non-ocular status of the patients with the DED symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, there has been little reported on any associations between the DED signs and symptoms [24]. On the other hand, multiple studies have examined the effects of the psychological influences including depression, anxiety, or feelings of subjective happiness on the subjective symptoms, and have reported finding a positive correlation [511]. In addition, pain sensitivity may also play a role in the DED symptoms.…”
Section: Introductionmentioning
confidence: 99%